Stryphnodendron adstringens: Clarifying Wound Healing in Streptozotocin-Induced Diabetic Rats - Pinto, Sandra Cristina Girotto; Bueno, Fernanda Giacomini; Panizzon, Gean Pier; Morais, Gutierrez; dos Santos, Paulo Victor Pires; Baesso, Mauro Luciano; Leite-Mello, Eneri Vieira de Souza; de Mello, João Carlos Palazzo (Planta Medica, 2015)
Diabetes mellitus is a serious public health problem in which a major complication is impaired wound healing. Among the strategies developed to foster tissue repair is the use of medicinal plants. The bark of Stryphnodendron adstringens, which is popularly used as an aid in wound healing, has a documented effect on wound repair in normal rats. This study evaluated the healing action of the crude extract of S. adstringens in diabetic rats, and its chemical content. Compounds present in the crude extract were characterized by mass spectrometry. In diabetic rats (streptozotocin 35 mg/kg), two wounds made in the skin were treated daily for 4, 7, 10, and 14 days with gel containing 1 % crude extract or with base gel. Histological analyses involved the measurement of the length and thickness of the re-epithelialized surface, quantification of the number of cells in mitosis, and types I and III collagen fibers. Also, cutaneous permeation by photoacoustic spectroscopy, and the expression of cyclooxygenase-2 and vascular endothelial growth factor by Western blot were assessed. The crude extract fingerprint showed masses indicating proanthocyanidins. The crude extract mainly stimulated cell migration and proliferation of keratinocytes at the beginning of the treatment in addition to stimulating the replacement of type III collagen fibers by type I collagen fibers at 10 and 14 days. The photoacoustic spectroscopy technique showed that the gel containing 1 % of crude extract permeated through the skin to the dermis, where the crude extract was found. Vascular endothelial growth factor was stimulated after 7 days of treatment with the crude extract and cyclooxygenase-2 at 4, 7, and 10 days. The crude extract of S. adstringens acted in tissue repair in wounds in diabetic rats by stimulating the production of collagen fibers at the wound site. The crude extract favored the formation of a more organized extracellular matrix and filled the entire extent of the wound, and also fostered the upregulation of cyclooxygenase-2 and vascular endothelial growth factor, which are essential to this process. These crude extract actions in diabetic wounds are probably due to the presence of proanthocyanidins.
Keywords: Stryphnodendron adstringens; Fabaceae; wound healing; diabetes in Wistar rats; photoacoustic spectroscopy; COX-2 and VEGF western blot; proanthocyanidins